Non-invasive monitoring of Streptococcus pyogenes vaccine efficacy using biophotonic imaging. - Faraz M Alam; Colin Bateman; Claire E Turner; Siouxsie Wiles; Shiranee Sriskandan (PLoS ONE)
Streptococcus pyogenes infection of the nasopharynx represents a key step in the pathogenic cycle of this organism and a major focus for vaccine development, requiring robust models to facilitate the screening of potentially protective antigens. One antigen that may be an important target for vaccination is the chemokine protease, SpyCEP, which is cell surface-associated and plays a role in pathogenesis. Biophotonic imaging (BPI) can non-invasively characterize the spatial location and abundance of bioluminescent bacteria in vivo. We have developed a bioluminescent derivative of a pharyngeal S. pyogenes strain by transformation of an emm75 clinical isolate with the luxABCDE operon. Evaluation of isogenic recombinant strains in vitro and in vivo confirmed that bioluminescence conferred a growth deficit that manifests as a fitness cost during infection. Notwithstanding this, bioluminescence expression permitted non-invasive longitudinal quantitation of S. pyogenes within the murine nasopharynx albeit with a detection limit corresponding to approximately 10(5) bacterial colony forming units (CFU) in this region. Vaccination of mice with heat killed streptococci, or with SpyCEP led to a specific IgG response in the serum. BPI demonstrated that both vaccine candidates reduced S. pyogenes bioluminescence emission over the course of nasopharyngeal infection. The work suggests the potential for BPI to be used in the non-invasive longitudinal evaluation of potential S. pyogenes vaccines.